Instrumen Evaluasi Bentuk Tes Berbasis HOTS Pada Mata Pelajaran Pendidikan Agama Islam - Yuliani, Yuliani (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
This article discusses the development and effectiveness testing of an evaluation instrument based on Higher Order Thinking Skills (HOTS) in the subject of Islamic Religious Education (PAI). The process of developing the HOTS-based evaluation instrument aims to enhance students' higher-order thinking skills in understanding and analyzing PAI concepts. The benefits of using the HOTS-based evaluation instrument in PAI learning include improving students' abilities in critical, analytical, and creative thinking. Implementing the HOTS-based evaluation instrument in exams or tests at schools can assist teachers in evaluating students' comprehensive and in-depth understanding of PAI materials. This article uses a qualitative method approach with the type of research being library research. It is hoped that this article will provide a positive contribution to the development of more effective evaluation methods in PAI learning.